Intraoperative transit time flow measurement in patients with diffuse coronary artery disease in the prevention of aortocoronary bypass graft occlusion - R. S. Akchurin; A. A. Shiryaev; V. P. Vasiliev; D. M. Galyautdinov; V. Yu. Zaikovsky; Sh. D. Mukimov (Кардиоваскулярная терапия и профилактика)
Aim. To study the parameters of transit time flow measurement (TTFM) for coronary bypass grafts in patients with diffuse lesions with different diameter of target coronary arteries.Material and methods. The study included 150 patients with diffuse coronary artery disease. All patients underwent microscope-assisted coronary artery bypass grafting (CABG), during which the TTFM parameters were evaluated. Depending on the diameter of target coronary arteries, patients were divided into 3 groups: group 1 included grafts to arteries ≤1 mm (n=101), group 2 — 1-1,5 mm (n=138), group 3 — ≥1,5 mm (n=308). Comparative analysis of TTFM parameters was performed.Results. Mostly participants were male (76%); mean age was 62,9±7,6 years. During hospitalization, we recorded 1 death, 2 perioperative myocardial infarctions (1,3%) and 1 cerebrovascular accident (0,7%). TTFM analysis showed the worst hemodynamic parameters and a higher rate of suboptimal function in group 1; blood flow parameters were comparable in groups 2 and 3. The additional analysis in group 1 and combined groups 2 and 3 allows us to make an opinion about the negative impact of coronary artery diameter less than 1 mm on optimal blood flow through the grafts (odds ratio=2,1, 95% confidence interval, 1,2-3,8, p=0,011).Conclusion. Diffuse coronary atherosclerosis with a diameter of target coronary arteries less than 1 mm significantly increase the risk of suboptimal graft function that requires considering more aggressive secondary prevention. TTFM demonstrate high effectiveness of microscope-assisted CABG in target coronary artery diameter of 1-1,5 mm and higher.